2010
DOI: 10.1159/000311729
|View full text |Cite
|
Sign up to set email alerts
|

Allometric Scaling of the Tectofugal Pathway in Birds

Abstract: Recent studies have shown that the relative sizes of visual regions in the avian brain are correlated with behavioral differences among species. Despite the fact that the tectofugal pathway is the primary source of visual input to the avian brain, detailed interspecific comparisons of the relative size of nuclei within the pathway, the optic tectum, nucleus rotundus and entopallium, are wanting. Here, we examine the allometric scaling relationships of each of these brain regions relative to the brain as a whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 204 publications
5
54
2
Order By: Relevance
“…In both forms of analysis, optic tectum volume, as determined using method S or method E with above correction factor, along with tegmentum volume, were both scaled against brain volume and mesencephalon volume. To account for bias that can exist when a specific brain region of interest is scaled against total brain volume (which includes the volume of the region of interest) [Deacon, 1990], optic tectum and tegmentum were also scaled against the brain volume remainder (BVR), which equals the total brain volume minus the volume of the brain region of interest [Deacon, 1990;Iwaniuk et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…In both forms of analysis, optic tectum volume, as determined using method S or method E with above correction factor, along with tegmentum volume, were both scaled against brain volume and mesencephalon volume. To account for bias that can exist when a specific brain region of interest is scaled against total brain volume (which includes the volume of the region of interest) [Deacon, 1990], optic tectum and tegmentum were also scaled against the brain volume remainder (BVR), which equals the total brain volume minus the volume of the brain region of interest [Deacon, 1990;Iwaniuk et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Given the differences in the organization of the visual streak between these two species [Bravo and Pettigrew, 1981;Wathey and Pettigrew, 1989] and other owls, it is plausible that differences in retinal topography may be reflected centrally in the organization of the optic tectum [Peterson, 1981]. There is some evidence that tectum volume scales very closely with total brain volume in owls [Iwaniuk et al, 2010b]; for example, data on tectum volume from similarly sized barn owl and burrowing owl brains (with volumes of 6,149 and 5,878 mm -3 , respectively) indicate that the tectum accounts for a very similar proportion of the brain in both species (2.22 and 2.53%, respectively). Insufficient information exists at present to speculate any further but a detailed comparative investigation of the retinorecipient brain areas in owls is under way [Gutiérrez-Ibáñez C, Iwaniuk AN, Lisney TJ and Wylie DR, unpubl.…”
Section: Retinotectal Projectionsmentioning
confidence: 99%
“…Such interordinal comparisons yield useful information on broad evolutionary patterns, but whether the same patterns hold true within orders or families is largely unknown [but see Iwaniuk et al, 2010a;Corfield et al, 2011]. In addition, little is known about interspecific variation in retinal topography in birds compared to other vertebrates, especially fishes and mammals [Collin, 1999[Collin, , 2008Iwaniuk et al, 2010b]. Here, we specifically examine eye shape and retinal topography within a single avian order, the owls (Strigiformes).…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies suggest that a transition from diurnality to nocturnality results in a reduction of the number of RGCs and a reduction of the tectofugal pathway [Kay and Kirk, 2000;Kirk and Kay, 2004;Hall et al, 2009;Iwaniuk et al, 2010b;Corfield et al, 2011]. Therefore, we would expect that nocturnal owl species have a relative smaller tectofugal pathway than more diurnal species.…”
Section: Introductionmentioning
confidence: 97%
“…In recent years, several studies have shown that different demands on the visual system in birds are correlated with variation in the relative size of visual areas in the brain Wylie, 2006, 2007;Iwaniuk et al, 2008Iwaniuk et al, , 2010bCorfield et al, 2011]. However, despite the compelling evidence that differences in activity patterns among owl species are reflected in the organization of the eyes, there has been no attempt so far to correlate these differences with variation in the relative size of visual regions in the brain.…”
Section: Introductionmentioning
confidence: 99%